Different visitation frequencies of native and non‐native bees to vines: how much vegetation is necessary to improve fruit production?. (16th September 2021) - Baronio, G. J.; Souza, C. S.; Silva, N. N. A.; Moura, N. P.; Leite, A. V.; Santos, A. M. M.; Maciel, M. I. S.; Castro, C. C.
Abstract: Pollination is provided by biodiversity and maintains global food production. We investigated the effects of vegetation cover on the abundance of floral visitor and vine ( Vitis labrusca Raf.) production. We expected an increase in both floral visitor frequencies and vineyard yields with an increase in native vegetation cover in the landscape. We also investigated different scenarios of visitor abundance with and without honeybees ( Apis mellifera L.). We surveyed floral visitors from ten vineyard plots with different native cover surrounding them and related both visitors and native vegetation to fruit set. Considering some of these vineyards, we compared physical and chemical traits of berries to understand how they vary according to native vegetation. Floral visitor abundance was positively related to native vegetation cover. However, considering only native bee abundance, we found a dual (hyperbolic) response. Apis mellifera (L.) Africanized was the most abundant species and had the highest number of interactions; however, when removed from the network analysis, the relationship between vineyards and native bees became more specialized. The fruit size and mass of berries differed among vineyards, as did some chemical traits related to commercial quality of fruits, such as soluble solids, pH and flavonoids. Vineyards surrounded by intermediate areas of native vegetation present a balance between resource availability from vineyards and native vegetation. Apis and non‐ Apis (such as flies and small bees) floral visitors, known to have different effects on vine pollination, could hypothetically provide variation in vine production and quality. Considering a near 20% native vegetation increment, there was an enhancement, on average, of ten‐fold more berries per bunch, the changing physical and chemical fruit traits by vegetation increment could also increase the aggregate value of vines and the value of pollination services in the economy. Abstract : Pollination is provided by biodiversity and maintains global food production. When we look to vineyards surrounded by intermediate native vegetation, we can observe a balance between the resource availability from vineyards and native vegetation.